The Effect of a Short Period of Supplementation with Glutamine Dipeptide on the Cognitive Responses after a Resistance Training Session of Women with HIV/AIDS: A Randomized Double-Blind Placebo-Controlled Crossover Study. (3rd April 2018) - Souza, Dayane Cristina de; Silva, Junior Cesar da; Matos, Felipe de Oliveira; Okano, Alexandre Hideki; Bazotte, Roberto Barbosa; Avelar, Ademar
Abstract : The aim of the present study was to investigate the effect of a short period of supplementation with glutamine dipeptide (GDP) on the acute responses to resistance training on the executive functions of people with HIV/AIDS. The sample consisted of 10 HIV+ women (45.00 ± 12.77 years old;65.71 ± 12.04  kg;1.54 ± 0.05  m) who were submitted to a randomized double-blind crossover procedure according to two experimental conditions: orally supplemented with 20 g/day of GDP or with maltodextrin for seven days. On the seventh day of supplementation all participants did cognitive function tests before and immediately after a resistance training session. Seven days of washout were adopted between conditions. Stroop andN -back tests were used to evaluate the executive functions. The training reduced the response time of each card in isolation and the latency time among them. GDP supplementation increased the magnitude of this effect, thus, reducing the latency time from the first to the last card in the Stroop test by almost 50% (P < 0.01 ). Considering theN -back test, there were no significant differences. It is suggested that GDP supplementation may increase the magnitude of the effect of an acute resistance training session in cognitive functions, particularly in the inhibitory control of people with HIV/AIDS. This trial is registered withNCT03236532 .